The relationship between cyberloafing levels and social media addiction among nursing students - Turan, Gulcan B.; ozer, Zulfunaz; Atan, Gulden (Wiley, 2021)
Purpose The study was conducted to examine the relationship between cyberloafing levels and social media addiction among nursing students in different cities (Erzurum, Istanbul, and Van) in Turkey. Design and Methods This study was comparative and descriptive in design, and the sample included 518 nursing students. Findings The average Cyberloafing Scale (CLS) total score of the students was 87.71 +/- 18.55, while the average Social Media Addiction Scale (SMAS) total score was 71.30 +/- 19.85. A positive and moderately significant relationship was found between the CLS and SMAS scores (p < 0.01). Practical Implications The cyberloafing and social media addiction levels of nursing students were found to be high. It was also found that the cyberloafing levels of the students increased as their social media addiction levels increased.
Keywords: cyberloafing; nursing students; social media addiction